Apnea during slow sub-anaesthetic infusion of intravenous ketamine for treatment-resistant depression - Marcos Gómez-Revuelta; María Fernández-Rodríguez; Laura Boada-Antón; Javier Vázquez-Bourgon (SAGE Publishing, 2020)
Ketamine's pharmacological profile makes it an interesting and useful drug to challenge treatment-resistant-depression (TRD). Emerging adverse events associated with single-slow-sub-anaesthetic doses for the treatment of depression are common, although generally transient and self-limited. Nevertheless, data on the safety of this practice are scarce. Thus, it seems timely before ketamine is used for clinical treatment of depression to recommend careful monitoring and reporting of all potential adverse events related to ketamine administration. Here, we describe a case of apnea during slow sub-anaesthetic infusion of intravenous ketamine for the treatment of resistant depression. As far as we are concerned, this is an uncommon, previously unreported, and potentially severe adverse event that clinicians should be aware of, and specific management measures should be implemented.